PERSEPSI PENGUNJUNG TERHADAP KUBU MARGHERITA SEBAGAI DESTINASI KUNJUNGAN DI KUCHING = (Visitors' Perception of Fort Margherita as a Visitor Destination in Kuching) - Shaik Azahar, Shaik Hussain; Athirah Shahira’a, Abdullah; Alicea Reshca, Seblie (Pernerbit UNISZA, 2023)
The purpose of this study is to investigate the potential of Fort Margherita, a historic building in Kuching, as a viable visitor destination. The building has garnered varied perceptions from visitors, and the objective of this research is to comprehend these perspectives and develop the site into a noteworthy tourist attraction that can contribute to the growth of the country's tourism sector. To achieve the research objectives, the researcher has employed a quantitative research method, which involved distributing 384 questionnaires to visitors in and around Fort Margherita. The gathered data will be analyzed to gain insights into visitors' perceptions and determine the necessary steps to meet the research objectives effectively. Through this study, the researcher aims to provide valuable information to stakeholders in the tourism industry, such as policymakers, government agencies, and tourism-related businesses. The findings will aid in enhancing the attractiveness of Fort Margherita as a tourist destination, thereby boosting the local economy and contributing to the sustainable development of the region.